Pelatihan Kompetensi Berbasis FQoL bagi Guru BK dalam Pendampingan terhadap Orang Tua dengan Anak Berkebutuhan Khusus - Rosita, Tita; Manuardi, Ardian Renata; Rahmawati Siddik, Riesa (Jurnal AbdiMU (Pengabdian kepada Masyarakat), 2022)
This community service activity aims to provide information and understanding to high school/equivalent Guidance and Counseling teachers in West Bandung Regency regarding the importance of Family Quality of Life (FQoL)-based counseling competencies for Guidance and Counseling teachers to improve counseling services in the process of mentoring parents who have children with special needs. Submission of material is done in the form of lectures and discussions. The results of this activity received a positive appreciation from Guidance and Counseling teachers that providing counseling services for parents of children with special needs based on FQoL can provide advocacy and strengthen parents' readiness in increasing interaction with children and optimizing parenting.